A new species of Andinopanurgus (Hymenoptera: Andrenidae) from high elevations in southern Peru - Gonzalez Betancourt, Victor Hugo (2019)
We describe and figure a distinctive new species of the bee genus Andinopanurgus Gonzalez and Engel (Andrenidae, Protandrenini) from Apurímac and Cusco in southern Peru. Andinopanurgus vargasllosai Gonzalez and Alvarado, n. sp., occurs at elevations above 4000 m in the Central Andes and is the second species of this genus in Peru. The new species possesses terga with semi-translucent distal margins, a unique feature among Andinopanurgus, and it combines morphological features of the two species groups previously recognized in the genus. To facilitate its recognition, we provide an updated key to species of Andinopanurgus.